2020
DOI: 10.3390/ijerph17020404
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of E-Gambling and of Problem E-Gambling in Poland

Abstract: This study estimated the levels of involvement in e-gambling and problem e-gambling in Poland and identified selected sociodemographic variables associated with e-gambling activities. The study was conducted using a representative sample of the adult inhabitants of Poland (n = 2000). The survey contained questions measuring three aspects of gambling (involvement in e-gambling, types of e-gambling activity, and problematic e-gambling). Results suggested that 4.1% of respondents were involved in e-gambling and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
0
13
0
3
Order By: Relevance
“…The problems studied are more specific IA problems rather than generalised IA (23% of the papers), which is a new trend on the field, and it is conversely opposite to the first two decades of research, in which IA was more prevalent than specific Internet use-related addiction problems. In order of frequency, in this second Special Issue, which was open to research on all addictive Internet and mobile phone use, the most prevalent problems ordered by frequency were: PMPU (38% [ 27 ]), IA (26% [ 16 ]), GD (23% [ 19 ]), SMA (18% [ 26 ]), OG (8% [ 39 ]), PUP (5% [ 37 ]), and PIS (3% [ 23 ]). This means the tendency before COVID-19 in the field was to study addictive problems related to the use of mobile technologies (e.g., PSU) and its risks, and this has increased during the pandemic [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The problems studied are more specific IA problems rather than generalised IA (23% of the papers), which is a new trend on the field, and it is conversely opposite to the first two decades of research, in which IA was more prevalent than specific Internet use-related addiction problems. In order of frequency, in this second Special Issue, which was open to research on all addictive Internet and mobile phone use, the most prevalent problems ordered by frequency were: PMPU (38% [ 27 ]), IA (26% [ 16 ]), GD (23% [ 19 ]), SMA (18% [ 26 ]), OG (8% [ 39 ]), PUP (5% [ 37 ]), and PIS (3% [ 23 ]). This means the tendency before COVID-19 in the field was to study addictive problems related to the use of mobile technologies (e.g., PSU) and its risks, and this has increased during the pandemic [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the purposes of screening pathological gamblers, we used SOGS, as developed by Lesieur and Blume (1987), as adapted for Poland in 2016 (Lelonek-Kuleta, Chwaszcz, Bartczuk, Niewiadomska, & Nowak, 2016). The maximum possible score in the questionnaire was 20 points.…”
Section: Methodsmentioning
confidence: 99%
“…Although the results are not consistent, the research most often shows a higher percentage of problem gamblers among online gamblers than offline gamblers (Canale et al, 2016;Effertz et al, 2018;Williams et al, 2012). The same was observed in Poland, where the symptoms indicating probable gambling addiction have occurred in 26.8% of online gamblers (Lelonek-Kuleta et al, 2020), while in Polish studies covering offline and online gamblers, 11.8% have displayed a risk (low to high) of gambling addiction (Moskalewicz et al, 2019). The study by Chóliz (2016) showed that in 2 years from legalizing online gambling in Spain, there was a nearly tenfold (from 2.53 to 24.21%) increase in the frequency of indicating this form of gambling as the leading cause of problems by patients seeking treatment for gambling addiction.…”
Section: Introductionmentioning
confidence: 95%